2
$\begingroup$

I am trying to find an infinitely differentiable function $f$ on $R$ with the same Taylor Series as $\sin x$ but $f(x)\ne \sin x$ for $x \ne 0$

I am having trouble with this question because to my knowledge there is no Taylor series that could fit this criteria

I know that the Taylor series for $\sin x$ is,

$$\sum_{n=0}^{\infty}(-1)^n\frac{x^{2n+1}}{(2n+1)!}$$

But is it possible to find an infinitely differentiable function $f$ on $R$ with the same Taylor Series as $\sin x$ but $f(x)\ne \sin x$ for $x \ne 0$? And if not, why?

$\endgroup$
  • 1
    $\begingroup$ Formatting tip: notice that if you enter $\sin x$ which gives $\sin x$, the function looks much better than if you enter $sin x$ which gives $sin x$. The same goes for logarithmic functions as well see $\ln x$ = $\ln x$ or $\log x$ = $\log x$ as opposed to $ln x$ = $ln x$ and $log x$ = $log x$ $\endgroup$ – user409521 Mar 20 '17 at 0:47
2
$\begingroup$

You can completely ignore the Taylor series of $\sin(x)$. What you want to find is a function $g(x)$ such that $0=g(0)=g'(0)=g''(0)=\dots$, but $g(x)\neq 0$ for $x\neq 0$. Then $f(x)=\sin(x)+g(x)$ will equal, and have the same derivatives as, $\sin(x)$ for $x=0$, but will differ from $\sin(x)$ elsewhere. One such function is:

$$ g(x)=\begin{cases}e^{-1/x^2}&x\neq0\\0&x= 0\end{cases}. $$

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ how would you calculate $g'(0)$ then? $\endgroup$ – us145 Mar 20 '17 at 0:43
  • 1
    $\begingroup$ The chain rule followed by taking limits should do the trick. $\endgroup$ – eyeballfrog Mar 20 '17 at 0:45
  • $\begingroup$ I vaguely recall that you show differentiability at zero by a clever application of L’Hospital’s Rule. $\endgroup$ – Lubin Mar 20 '17 at 1:18
  • $\begingroup$ @Lubin.Let $g^n$ be the $n$th derivative of $g$, with $g^0=g.$ Then $g^n(x)=P_n(1/x)e^{-1/x^2}$ for $x\ne 0,$ where $P_n$ is a polynomial. Suppose $g^n(0)=0$.For $x\ne 0$ let $x=1/y.$ Then $(g^n(x)-g^n(0))/(x-0)=$ $yg^n(1/y)$ $=yP_n(y)/e^{y^2}.$ And $y\to \infty$ as $x\to 0,$ while $e^{y^2}$ grows faster than any polynomial as $y\to \infty$ because $e^{y^2}>y^{2n}/n!$ when $y\ne 0.$ Hence $g^n(0)=0\implies g^{n+1}(0)=0.$ $\endgroup$ – DanielWainfleet Mar 20 '17 at 11:12
  • $\begingroup$ @Lubin. My previous comment should say : $e^{y^2}$ grows faster than $yP_n(y)$ as $y\to \infty$ because $e^{y^2}>y^{2+2\deg (P_n)}/(1+\deg (P_n))!$ when $y\ne 0$. I ran out of editing time, which for me is mostly typo-correction time. $\endgroup$ – DanielWainfleet Mar 20 '17 at 11:26

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.